Acute effects of an ergometer-based dryland alpine skiing specific high intensity interval training - Stöggl, T.; Kröll, J.; Helmberger, R.; Cudrigh, M.; Müller, E. (Frontiers in Physiology, 2018)
Introduction: To establish an alpine ski racing (ASR) specific dryland high intensity training protocol (HIT), we set out to analyze cardiorespiratory and metabolic responses of three ASR specific HIT modes using a ski ergometer compared with a running HIT.